LINGUAGEM, CULTURA E VARIAÇÃO: A ABORDAGEM DOS ADJETIVOS NOS LIVROS DIDÁTICOS DO ENSINO MÉDIO - BAIL, EVERALDO (2020)
This thesis, with the theoretical-methodological support of Variationist Sociolinguistics, describes and analyzes the approach of linguistic variation in working with adjectives, in the textbooks of Portuguese in High School, in Guarapuava, Paraná. For this purpose, it brings up the survey of the titles suggested by the teachers and selects for analysis the two most indicated textbooks in this survey: the first one, from the collection “Se liga na Língua: Literatura, Produção de Texto, Linguagem”, by Ormundo and Siniscalchi (2016); the second one, from the collection “Novas Palavras – Literatura, Gramática, Leitura e Produção de Texto”, by Amaral et al (2016). The didactic materials analyzed carry the contents related to Sociolinguistics consistently with the theoretical assumptions of this area of Language Studies, adequately presenting linguistic variation, its varieties and other specific approaches, such as linguistic adequacy and inadequacy. In terms of the adjectives, the qualitative analyzes, separately and in comparison, realized in this study attest to the pertinence and coherence of the application of the sociolinguistic perspective in the selected textbooks, promoting a necessary and current reflection on the language in use, without the need for lists of adjectives, adjective phrases and nomenclatures.